ANALYSIS OF THE IMPLEMENTATION OF THE SINDAR RAYA HEALTH INSURANCE SYSTEM PROGRAM SIMALUNGUN REGENCY - Dilla Sastia Mara; Hendri Kurniawan; Shofian Syarifuddin (International Conference on Health Science, Green Economics, Educational Review and Technology, 2021)
Most of the Sindar Raya community is a lower middle class society, although there are still a small number of upper middle class people. The type of research used in this study uses a qualitative approach with in-depth interviews with sources of information so that it is clear and more in-depth about the implementation of the JKN program at the Sindar Raya Health Center in May-July 2017. The human resources of the Sindar Raya Health Center are still lacking in quantity and quality. However, in health services, there is no fundamental difference between the services before JKN and the current JKN era. Resource administration capabilities are still not ready to apply the JKN reporting format. Facilities and infrastructure are still lacking, but the puskesmas can still maximize health services to the community. Medical facilities that are still incomplete are dental health services and laboratories. Administrative support facilities such as computers and the internet are still incomplete and must be fulfilled immediately. Financial resources to support the Sindar Raya Health Center are available. In terms of fragmentation, the bureaucratic structure has been running in accordance with the duties and roles of each. Meanwhile, the operational standards for implementing JKN are also clear. Health services in JKN in the field can be carried out because there are no fundamental differences in providing health services. Sindar Raya Health Center in an effort to improve health services to be more active in order to be able to implement the JKN program optimally. Administrative support facilities such as computers and the internet are still incomplete and must be fulfilled immediately. Financial resources to support the Sindar Raya Health Center are available. In terms of fragmentation, the bureaucratic structure has been running in accordance with the duties and roles of each. Meanwhile, the operational standards for implementing JKN are also clear. Health services in JKN in the field can be carried out because there are no fundamental differences in providing health services. Sindar Raya Health Center in an effort to improve health services to be more active in order to be able to implement the JKN program optimally. Administrative support facilities such as computers and the internet are still incomplete and must be fulfilled immediately. Financial resources to support the Sindar Raya Health Center are available. In terms of fragmentation, the bureaucratic structure has been running in accordance with the duties and roles of each. Meanwhile, the operational standards for implementing JKN are also clear. Health services in JKN in the field can be carried out because there are no fundamental differences in providing health services. Sindar Raya Health Center in an effort to improve health services to be more active in order to be able to implement the JKN program optimally. Meanwhile, the operational standards for implementing JKN are also clear. Health services in JKN in the field can be carried out because there are no fundamental differences in providing health services. Sindar Raya Health Center in an effort to improve health services to be more active in order to be able to implement the JKN program optimally. Meanwhile, the operational standards for implementing JKN are also clear. Health services in JKN in the field can be carried out because there are no fundamental differences in providing health services. Sindar Raya Health Center in an effort to improve health services to be more active in order to be able to implement the JKN program optimally.